Innovation in Sustainable Plastic Waste Management through Ecobrick Technology as an Effort to Realize an Environmentally Friendly Village - Devy Siti Khofifah; Rosanna Wulandari; Eris Juliansyah (Siber Nusantara Research, 2026)
The problem of plastic waste is still a serious challenge in environmental management, especially at the village level which has limitations in an integrated waste management system. The accumulation of plastic waste that is not managed properly can have a negative impact on the environment and public health. This Community Service Activity (PKM) aims to implement innovations in sustainable plastic waste management through ecobrick technology by involving the community and students as agents of change in realizing environmentally friendly villages. The method of implementing activities uses a participatory-educational approach which includes the preparation stage, socialization, ecobrick making training, collaborative implementation between the community and schools, and monitoring and evaluation. The results of the activity show that there is an increase in public and student knowledge about plastic waste management, an increase in skills in making ecobricks, and the beginning of behavioral changes in reducing and sorting plastic waste at the source. The involvement of students has proven to be effective in expanding the impact of environmental education to families and the surrounding community. However, the sustainability of the program still requires institutional strengthening and sustainable mentoring. In conclusion, ecobrick technology based on community and student participation is an effective strategy in supporting sustainable plastic waste management and realizing environmentally friendly villages.